ENVIRONMENTAL INFORMATION DISCLOSURE TERHADAP FINANCIAL PERFORMANCE DENGAN NILAI PERUSAHAAN SEBAGAI PEMODERASI: PENDEKATAN GAYA PENGUNGKAPAN - MIFTHAKUL JANAH; SUSI HANDAYANI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2020)
Companies with a high level of sensitivity to environmental problems will disclose social responsibility reports and sustainability reports as a form of awareness. There is no environmental disclosure standard, causing disclosure to be voluntary, so this study divides the two types of disclosure styles (substantive and symbolic styles). This study aims to determine the effect of EID on financial performance with firm value as a moderating variable with a two-style disclosure approach. The sample in this study was high profile companies listed on the Indonesia Stock Exchange 2017-2018 with 400 samples total divided into two types disclosures through a purposive sampling technique. Data analysis techniques used multiple linear regression and Moderated Regression Analysis through SPSS 25. The results showed that both the subtantive and symbolic EID styles had a positive effect on financial performance, because the more total EID subtantical and symbolic styles, the more financial performance improved. Then the company's value can moderate the effect of EID on the financial performance of a substantive style company, while the effect of EID on the financial performance of a symbolic style company cannot be moderated by the value of the company, because the substantive style can increase investor confidence through quantitative and actual information disclosed, while the symbolic style is impressed greenwashing in its disclosure so that it cannot give investors confidence.